Eksotisme dan pencitraan perempuan pribumi dalam novel Tjerita Njai Dasima - Esaliana, Dias; Cinthya, Nathasha; Susanto, Dwi (citeus, 2021)
This study intends to show the self-image of Indonesian women who are considered ‘exotic’ in Gijsbert Francis’ novel Tjerita Njai Dasima. The term exotic refers to alienation and othering Europeans raised towards the eastern world, especially Indonesia. The author discusses the image of Indonesian women featured in the novel Tjerita Njai Dasima through the point of view of postcolonial feminists using a qualitative descriptive method by displaying the result based on subject relations and imagery built in the novel. The data in the discussion focuses on the contents of literary works dealing with postcolonial discourse, which brings out the construction of identity towards women based on the reality that women are often seen as symbolic images and objects of male invaders. Penelitian ini bertujuan untuk menunjukkan citra diri perempuan Indonesia yang digambarkan sebagai sesuatu yang dianggap ‘eksotik’ dalam novel Tjerita Njai Dasima karya Gijsbert Francis. Eksotik yang dimaksudkan merupakan suatu keasingan dan keliyanan yang dimunculkan oleh bangsa Barat terhadap dunia Timur, khususnya Indonesia. Penulis membahas citra perempuan Indonesia yang ditampilkan dalam novel Tjerita Njai Dasima melalui sudut pandang feminis pascakolonial menggunakan metode deskriptif kualitatif yakni dengan menampilkan hasil berdasarkan relasi-relasi subjek dan pencitraan yang dibangun dalam novel Tjerita Njai Dasima versi Gijsbert Francis. Data pada pembahasan difokuskan pada isi karya sastra yang mengandung wacana pascakolonial yang memunculkan konstruksi identitas terhadap perempuan. Perempuan sering dianggap sebagai gambaran simbolis dan objek dari pria yang menjajah.